Molecular dynamics simulations of thermal boundary resistances in a liquid between two solid walls separated by a nano gap. (October 2016) - Wang, Xu; Cheng, Ping; Quan, Xiaojun
Abstract: Molecular dynamics simulations are performed to study heat conduction in a liquid argon between two copper walls separated at a nano distance. Effects of wall wettabilities and separation distances on thermal boundary resistances of two solid–liquid interfaces at a constant heat flux are obtained. Simulation results show that the thermal boundary resistance consists of two parts in series: (i) the resistance between solid walls and the nanolayer absorbed on it, and (ii) the resistance between the nanolayer and bulk liquid or the other nanolayer if there is no bulk liquid in between. While the first part of thermal boundary resistance has already been widely studied, the second part is often overlook which is the subject of discussion in this paper. When the solid wall becomes more and more hydrophilic, the first part decreases while the second part has the opposite trend which leads to a minimum thermal boundary resistance. The increase of the second part of resistance with increasing wall wettability can be explained by: (i) larger differences in vibrational densities of states (VDOSs) of the nanolayer and the bulk liquid, which indicates that atoms in both sides are more difficult to be in resonance, leading to weaker heat conduction and (ii) less atom exchange between the nanolayer and liquid atoms bulk liquid or the other nanolayer, leading to less atomic energy exchange between the nanolayer and bulk liquid. With the separation distance becoming larger, the thermal boundary resistance increases at first and then approaches a constant value asymptotically.